First record of Clavulina fuscolilacina (Cantharellales, Basidiomycota) for Mexico - Uitzil Colli, Michael Oswaldo; De la Fuente, Javier Isaac; Arana Yepez, Beni Josue (Instituto de Ecología, A.C., 2021)
Background and Aims: The genus Clavulina belongs to the Hydnaceae family (Cantharellales, Basidiomycota). They have ectomycorrhizal habits and are located in both temperate and tropical forests; the highest species diversity is found in the latter. The purpose of this document is to contribute to the knowledge of the Mexican tropical funga, specifically in the Yucatán Península. Methods: Collection of the specimens was carried out in the states of Quintana Roo and Yucatán, in coastal vegetation and deciduous lowland tropical forests, respectively. The general mycological protocols for collecting, characterizing, and curating the basidiomas were followed. The specimens are deposited in the herbaria ITCV of the Instituto Tecnológico de Ciudad Victoria and UADY of the Universidad Autónoma de Yucatán. Key results: Clavulina fuscolilacina is characterized by claviform or branched basidiomas, lilac or gray in color. It grows gregarious under Polygonaceae like Coccoloba uvifera and Gymnopodium floribundum, possibly forming an ectomycorrhizal association. Previously, this species was known only from Brazil, so this record expands its distribution range to Mexico. Moreover, a taxonomic key of the genus Clavulina for Mexico is presented. Conclusions: The first record of the genus Clavulina for the Yucatán Península is presented. Furthermore, this is the first report of C. fuscolilacina from Mexico and beyond Brazil.